THE VALUE OF DETERMINING THE ROLE OF CARTILADIC OLIGOMERIC MATRIX PROTEIN (COMP) IN THE EARLY DIAGNOSIS OF OSTEOARTHRITIS - Buranova, Sagdiyana. N.; Akhmedov, Khalmurad. S.; Kholmurodov, Davron. M. (Educational Research in Universal Sciences, 2023)
60 patients with radiologically determined 0-II stages of knee joint osteoarthritis aged 50.3±4.4 years old with average duration 5.4±3.6 years were involved in the study. At the same time 10 healthy individuals (average age 47.5±7.1years old) of the age and gender compatible with the patients of OA group were also enrolled in the study. According to the results of the study radiological stage of osteoarthritis, progression and duration are characterized by certain structural changes. Within pre-radiological stage rise of cartilage oligomeric matrix protein (COMP) in blood serum indicates early destruction of cartilage.